Asesmen Potential Review pada Pegawai Pelabuhan PT.X (Umpan balik: Pengembangan Kompetensi Melalui Konseling) - Andi Muhammad Aditya; Nur Pratiwi Noviati (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2021)
PT.X is a service business-oriented company in Indonesia, namely in the port service sector. In order to increase HR competency, PT.X regularly conducts potential reviews on several classes of positions including senior analysts, senior assistant managers, and senior managers. The research objective was to determine the actual condition of the employees' competencies. Data collection methods used were psychological tests, observation, interviews, and LGD. Data analysis used qualitative and quantitative descriptive analysis. The subject in this study was a 44 year old woman who was an employee at PT. X in the supporting facilities subdivision (FP) who has a structural position as Assistant Senior Manager (ASM). The results showed that from the entire series of assessments carried out to Ms.Y, it showed that there were 10 competencies that met the standards, 3 competencies in the category above the standard, and 1 competency below the standard. This means that generally Ms.Y meets the standards of her current position. The conclusion from this potential review assessment shows that Ms. Y meets the competency standards in her position as ASM in the supporting facilities subdivision, however, further development is needed regarding substandard competencies using counseling training so that Ms.Y can implement it to subordinates.